2020
DOI: 10.1108/bl-02-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

The facts of continuing professional development for LIS professionals in Pakistan: a literature review

Abstract: Purpose Continuous professional development is an essential in-service and on-going learning process that provides an opportunity to young and mid-career professionals to update and align their skills in connection with the contemporary needs of library users. This study aims to identify and synthesize the literature on continuing professional development (CPD) opportunities for Pakistani librarians and information professionals. Design/methodology/approach This study is based on descriptive literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The lack of expertise of DTEs to accomplish mentoring tasks properly is the main cause for the poor output of TPSs against CPD activities. The findings of this research work partly agree with the results of Saleem and Ashiq (2020), who highlighted the great need to review the program of teacher mentoring to set goals for the enhanced professional skills of teachers. Abdullah (2020) examined whether the use of teacher diaries, regular assignments, and monitoring of HW and activity-based teaching and maintenance discipline in the classroom has improved.…”
Section: B Perceptions Of the Key Stakeholders About The Positive Ansupporting
confidence: 85%
“…The lack of expertise of DTEs to accomplish mentoring tasks properly is the main cause for the poor output of TPSs against CPD activities. The findings of this research work partly agree with the results of Saleem and Ashiq (2020), who highlighted the great need to review the program of teacher mentoring to set goals for the enhanced professional skills of teachers. Abdullah (2020) examined whether the use of teacher diaries, regular assignments, and monitoring of HW and activity-based teaching and maintenance discipline in the classroom has improved.…”
Section: B Perceptions Of the Key Stakeholders About The Positive Ansupporting
confidence: 85%
“…This was also a period of growing ICT demand in the libraries while the responsible bodies did not work seriously or jointly. The department of libraries, the National Library of Pakistan and PLA failed to produce visionary library professionals (Dub e et al, 2005;Saleem and Ashiq, 2020). Similarly, the skills required for library jobs in Pakistan were changing and have an emphasis on information and technology, especially automation (Qutab and Shafique, 2011).…”
Section: Lis Virtual Communities In Pakistanmentioning
confidence: 99%
“…They suggested skilled professionals, library schools, the national library association and the higher education commission should provide mentorship and training to young professionals Ameen (2011). indicated the need of training for LIS professionals in areas of library software, electronic library tools and searching techniques Saleem and Ashiq (2020). conducted a systematic literature review on the CPD for the Pakistani library professionals and concluded that information technology skills are much needed for academic librarians in Pakistan to cope with the changing needs of current and prospective library users.…”
mentioning
confidence: 99%
“…According to the IFLA Guidelines for continuous professional learning (CPL) (Varlejs, 2016;de Alwis Jayasuriya et al, 2021), there is a gap in the research on professional development in the LIS sector; likewise, there are no comprehensive studies about how or if openness is included in Library and Information Science (LIS) programmes. However, there are some interesting studies regarding continuing education for LIS professionals in the South and South-East Asian Regions (such as Pakistan, Maldives, and Indonesia) (Saleem and Ashiq, 2020;de Alwis Jayasuriya et al, 2021) and some studies about the general development of library staff (Welz, 2017;Haglund et al, 2018).…”
Section: Introductionmentioning
confidence: 99%